Draft Five Year Plan 1978-83 Vol - I Review Perspective Policy Government of Assam - Planning Commission (Planning Commission, 1978)
Assam has a predominantly rural population with less than 10% of its population living in urban areas as compared with 20% for the country. The total number of towns in the State has increased from 53 in 1961 to 72 in 1971. Guwahati is the only town which has a population of over one lakh. There are four towns with a population between 0.5 to one lakh. The following table gives the growth in the number of Town committee municipalities and Municipal Corporations over the period 1961-1978.
Government of Assam, Planning and Development Department
Planning and Development Department Government of Assam